FOLK DANCE ‘DHAMAIL’ OF SURMA-BRAAK VALLEY: A CRITICAL ANALYSIS - Dr. Banobrata Aditya (IJRDO - Journal of Social Science and Humanities Research, 2019)
Dhamail is an important and most popular folk song and folk culture of Surma Brak Valley. It is a more artistic and vigorous dance as well as folk songs of ancient Srihatta and Cachar. Dhamail Dance depends on various elements like whole body movements. This article explores the themes of Radha Krishna Dance formation and the chemistry between them we get a glance through the form of Dhamail. Specifically Dhamail is performed newly known places like Kaimganj, Hailkandi, Cachar, Sylhet, Maymasingh, Maulabi bazar and its surrounding areas. It was originally composed by Radharaman Dutta, Kabi Sharad and other prominent figures